Hubungan Antara Konsumsi Tablet Fe Saat Menstruasi dengan Kejadian Anemia pada Remaja Putri di Desa Wirengan Masaran Sragen - Anik Sulistiyanti; Ana Yuliana; Weri Veranita (Indonesian Journal on Medical Science, 2022)
Anemia in women generally occurs during menstruation, pregnancy, childbirth, postpartum and breastfeeding in a woman's reproductive cycle. In young women, anemia problems will appear due to malnutrition or during menstrual conditions. The main cause of anemia in women is the decreased intake of foods made from iron (Fe) so that the need for iron (Fe) increases due to blood loss during menstruation. The purpose of this study was to determine the relationship between consumption of Fe tablets during menstruation and the incidence of anemia in adolescent girls in the village of Wirengan Masaran, Sragen. The research method used was analytical research with a cross sectional approach. Using simple random sampling technique with a sample of 50 female adolescent girls in Wirengan Masaran Village. The research instrument was examination of anemia, administration of Fe tablets and digital HB measurements. Data analysis used univariate analysis and bivariate analysis, namely chi quare. The results showed that 18 respondents (16.0%) were not anemic and who took Fe tablets during menstruation, while 19 respondents were anemic and did not consume Fe tablets. Based on the results of the Chi Square test, the p value = 0.003 < 0.05 with p value can be concluded that Ha is accepted. There was a relationship between consumption of Fe tablets during menstruation and the incidence of anemia in adolescent girls in the village of Wirengan Masaran, Sragen.